Penerapan Model Pembelajaran Kooperatif Berbantuan Media Audio Visual dalam Meningkatkan Hasil Belajar Akidah Akhlak di MTs Negeri 2 Kota Padang - S, Rahmad; Sabri, Ahmad; Hidayati, Hidayati (Lembaga Yasin AlSys, 2024)
This study aims to examine the effect of a cooperative learning model assisted by audiovisual media on the learning outcomes of Akidah Akhlak among eighth-grade students at MTs Negeri 2 Kota Padang. The research employed a quantitative approach with a quasi-experimental design, specifically a randomized control group only design, involving an experimental class (VIII.3) and a control class (VIII.4). Data were collected through tests, questionnaires, performance assessments, and documentation. The findings indicate that students' knowledge aspect scores in the experimental class were higher, with an average score of 83.70 compared to 76.75 in the control class, with t calculated (5.26) t table (1.69). For the attitude aspect, the experimental class achieved an average score of 87, outperforming the control class, which scored 81.5, with t calculated (4.51) t table (1.69). Similarly, for the skill aspect, the experimental class scored an average of 82.83, compared to 73.39 in the control class, with t calculated (6.09) t table (1.69). Overall, the results demonstrate that the cooperative learning model assisted by audiovisual media not only enhances students' comprehension but also significantly impacts their attitudes and skills. Based on these findings, it can be concluded that this learning model is more effective than conventional methods in improving Akidah Akhlak learning outcomes, particularly in the topic “Miracles and Other Extraordinary Events.”.